When Lola Visits - Sterling, Michelle; Asis, Aaron Paul (New York, NY : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2021)
"For one young girl, summer is the season of no school, of days spent at the pool, and of picking golden limes off the trees. But summer doesn't start until her lola--her grandmother from the Philippines--comes for her annual visit"--Dust jacket flap.
Keywords: Summer -- Juvenile fiction; Grandmothers -- Juvenile fiction; Grandparent and child -- Juvenile fiction; Filipino Americans -- Juvenile fiction; Cooking, Philippine -- Juvenile fiction; Summer -- Fiction; Grandmothers -- Fiction; Grandparent and child -- Fiction; Filipino Americans -- Fiction; Cooking, Philippine -- Fiction; Picture book